Mapping of Clinical Documentation to Ontology - Pacheco, Edson José; Nohama, Percy; Schulz, Stefan (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2009)
Clinical documentation requires the representation of fine-grained descriptions of patients' history, evolution, and treatment. These descriptions are materialized in findings reports, medical orders, as well as in evolution and discharge summaries. In most clinical environments natural language is the main carrier of documentation. Written clinical jargon is commonly characterized by idiosyncratic terminology, a high frequency of highly context-dependent ambiguous expressions (especially acronyms and abbreviations). Violations of spelling and grammar rules are common. The purpose of this work is to map free text from clinical narratives to a domain ontology. To this end, natural language processing (NLP) tools will be combined with a heuristic of semantic mapping.